Rules for school - Greven, Alec (Collins, 2010)
School is hard! There's a lot to know, like where to sit on the bus, how to find your way around the halls, and what to do to make sure you stay on your teacher's good side. Lucky for you Alec Greven has just turned eleven, and he's seen it all. Alec passes down his sixth-grade wisdom and gives advice that will help every student who's starting out or just started out on the wrong foot.